Définir le sens dans un réseau lexical - Sikora, Dorota (Studia Romanica Posnaniensia, 2012)
As underlined in Wierzbicka (1996: 239), a «linguistic definition is a scientific hypothesis about the concept encoded in a given word». The present paper focuses on the problem of what such hypothesis is about. Lexicon of any language is structured with a set of connections relating lexical items. That is to say that speakers of any language need to master not only separate words, but rather a cluster of connected senses. If so, then a lexical definition should lay out the concept the word lexicalizes in the way that gives access to the whole grasp of its conceptual, paradigmatic and syntagmatic relations. We discuss the topic of definitional structures developed in the context of the French Lexical Network (Réseau Lexical du Français).